Three-dimensional culture of a genetically modified hepatoma cell line using macroporous gelatin beads - Tonello, Jane Marie (Cytotechnology, 2017)
Hepatoma cells are a candidate cell source for bio-artificial livers. However, they exhibit reduced liver functions compared with primary hepatocytes. In our previous study, genetically engineered mouse hepatoma cells were created by transduction with vectors mediating inducible overexpression of eight liver-enriched transcription factors. Upon the induction of the liver-enriched transcription factors transduced, the cells expressed both phenotypic and genotypic liver functions at high levels. In the present study, we performed three-dimensional culture of these cells using macroporous gelatin beads. When immobilized on the macroporous gelatin beads, these cells exhibited further enhancement in liver functionality, including increased albumin secretion, ammonia removal and cytochrome P450 activity. The levels of these functions were significantly enhanced compared to monolayer culture. The method is simple and scalable, and provides highly functional cells that can be used in basic and applied fields of hepatic research.